Впровадження циркулярної економіки на основі європейського досвіду - Горбаль, Н. І.; Мазурик, М. М.; Микитин, О. З.; Horbal, N. I.; Mazuryk, M. M.; Mykytyn, O. Z. (Видавництво Львівської політехніки, 2021)
Прискорений приріст населення планети, вичерпання природніх ресурсів, надмірне забруднення навколишнього середовища, що несе загрозу існуванню людства, стало передумовою появи у світі концепції циркулярної економіки та принципів сталого розвитку, тобто ведення бізнесу без шкоди для середовища. Модель циркулярної (кругової) економіки спрямовано на енергозбереження, регенеративне екологічно чисте споживання та виробництво. Викладено результати дослідження концепції циркулярної економіки та переваг її впровадження на основі досвіду Європейського Союзу – глобального лідера в цій сфері. Розкрито основні цілі, пріоритети та заходи ЄС при впровадженні кругової економіки. Висвітлено основні принципи циркулярної економіки, наведено приклади успішного використання її бізнес-моделей. Визначено дві найактуальніші глобальні проблеми, які може вирішити лише економіка замкненого циклу, подано прогнози результатів її глобального використання.

Accelerated population growth, depletion of natural resources, excessive pollution of the environment, which threatens the existence of mankind, was a prerequisite for the emergence of the concept of circular economy and the principles of sustainable development, ie doing business without harm to the environment. The model of circular (circular) economy is aimed at energy saving, regenerative environmentally friendly consumption and production. The article presents the results of the study of the concept of circular economy and the benefits of its implementation based on the experience of the European Union – a global leader in this field. The main goals, priorities and measures of the EU in the implementation of the circular economy are revealed. The basic principles of the circular economy are highlighted, examples of successful use of its business models are given. The two most acute global problems that can be solved only by a closed-loop economy are identified, and forecasts of the results of its global use are given. Closed-loop economics is a concept of resource management that is rapidly gaining global popularity and is recognized in the scientific literature as one of the key drivers for achieving objectives of the Paris Agreement. 30 years have passed since the first mention of the “circularity” of the economy, however only after its official introduction in the EU its popularity has grown rapidly, and world leaders have gradually been realizing its importance for achieving sustainable development. Climate change and depletion of natural resources are the visible negative processes that require the implementation of a circular economy. At the same time, society itself must change – from the choice of raw materials, product development methods and new concepts of service to the widespread use of by-products of one industry as complete raw materials for another. This requires the training of relevant specialists, whose professional activity will be the circular economy.To date, the most significant results in the transition to a circular economy are demonstrated by the European Union (EU), where the European Resource Efficiency Platform, which brings together EU countries, aims to ensure the transition to a circular economy based on reuse and high-quality recycling. Circular economy is a new trend that is seen as an important area of structural reform and aims to raise awareness of the real environmental, energy and socio-economic situation of the world by identifying ideological options for a better understanding of the dilemma of economic growth vs. the environment, optimal ways and more effective tools for solving problems, faced by society. The goal of the circular economy is to ensure, in line with the global CSWs, a shift towards sustainable production and consumption while integrating environmental issues into the adoption process solutions.
Implementation of circular economy on the basis of European experie
Keywords: циркулярна економіка; економіка замкненого циклу; кругова економіка; зелена економіка; сталий розвиток; повторне використання; бізнес-модель; circular economy; closed-loop economy; circular economy; green economy; principles of circular economy; sustainable development; reuse; business model; 330.3